Internship and Monograph reports entitled ”Nano- and microparticle-stabilized Pickering emulsions designed for therapeutic and cosmetic applications" - Peito, Sofia Gonçalves Pires (2020)
Relatório de Estágio do Mestrado Integrado em Ciências Farmacêuticas apresentado à Faculdade de Farmácia